Physiologically based pharmacokinetic evaluation of cefuroxime in perioperative antibiotic prophylaxis - Rimmler, Christer (Br J Clin Pharmacol, 2019)
AIMS: Adequate plasma concentrations of antibiotics during surgery are essential for the prevention of surgical site infections. We examined the pharmacokinetics of 1.5 g cefuroxime administered during induction of anaesthesia with follow‐up doses every 2.5 hours until the end of surgery. We built a physiologically based pharmacokinetic model with the aim to ensure adequate antibiotic plasma concentrations in a heterogeneous population. METHODS: A physiologically based pharmacokinetic model (PK‐Sim(®)/MoBi(®)) was developed to investigate unbound plasma concentrations of cefuroxime. Blood samples from 25 thoracic surgical patients were analysed with high‐performance liquid chromatography. To evaluate optimized dosing regimens, physiologically based pharmacokinetic model simulations were conducted. RESULTS: Dosing simulations revealed that a standard dosing regimen of 1.5 g every 2.5 hours reached the pharmacokinetic/pharmacodynamic target for Staphylococcus aureus. However, for Escherichia coli, >50% of the study participants did not reach predefined targets. Effectiveness of cefuroxime against E. coli can be improved by administering a 1.5 g bolus immediately followed by a continuous infusion of 3 g cefuroxime over 3 hours. CONCLUSION: The use of cefuroxime for perioperative antibiotic prophylaxis to prevent staphylococcal surgical site infections appears to be effective with standard dosing of 1.5 g preoperatively and follow‐up doses every 2.5 hours. In contrast, if E. coli is relevant in surgeries, this dosing regimen appears insufficient. With our derived dose recommendations, we provide a solution for this issue.